The urgency of Education and Language research: to study the human body through the lens of art(s) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Review of the book Bakhtin e as artes do corpo, edited by Beth Brait and Jean Carlos Gonçalves. This work is the third volume of the LiCorEs Collection: Language, Body, Aesthetics. The volume starts with a Foreword by the two organizers and it contains five essays which bring to the heart of the debate some notions, concepts and reverberations of the arts of the body in dialogue with their discursive elements with Bakhtinian studies in a perspective which is also open to other aspects of knowledge.
Keywords: Body; Art; Language; Bakhtin